Mapeamento de áreas de suscetibilidade e risco de inundação de trecho do rio Uruguai no município de São Carlos - SC - França, Jacson Rodrigues (2017)
Based on the problems of riverside flooding, especially when the rivers are located in urban areas, the present study had the objective of analyzing flood data from the Uruguay River downstream of the UHE Foz do Chapecó, in order to map the areas Susceptibility and flood risk in the right bank of the river, in the municipality of São Carlos-SC. It was used as a base tool the Digital Land Model produced and made available by the Secretariat of Sustainable Economic Development of Santa Catarina (SDS), seeking with the mapping that the results serve as tools in the development of public policies for territorial management and actions in cases of loss . For the development of the susceptibility map, the crossing between slope classes and level quotas reached at different Flood Return Times was performed. For the mapping of risk, adaptations of cartographic methodologies developed in some works carried out in Brazil that relate natural components such as level quotas reached by floods with different return times, with anthropic components related to land use and occupation, were used. In the mapping of susceptibility, areas of low susceptibility predominated (45.8%). Already areas designated as Very High Susceptibility represent 4.6% and High Susceptibility 11.3% of the studied area, and indicate not to be propitious to the occupation. Regarding the mapping of risk, it was possible to conclude that due to the morphological and geological characteristics, a methodology presented more significant results, considering the spatialization of the households located in flood zones affected by several times of Return. According to the map of Risco, in the Águas do Prata neighborhood, the dwellings allocated in flood zones with a time of return of 20 and 74 years do not run High and Very High Risk. In relation to the houses that are in flood zones with a return time of 2 years, 28.18% have Very High Risk, while 72.96% of the dwellings located in flood zones with probability of 5 years of return in the same Neighborhood are in High Risk area. The other methodology may be indicated for flatter areas where valleys are shallower and floods of Return Times less than 5 years reach larger areas with larger numbers of dwellings.